2017
DOI: 10.1080/1573062x.2017.1279187
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of swales on receiving water quality

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Grass swales are vegetated open channels usually designed to convey runoff, reduce rainfall runoff by infiltration and boost the runoff quality from filtration through the soil media [ 11 , 12 , 13 , 14 , 15 ]. Grass swale uses different kind of vegetation, which can infiltrate the surface water into the underground soil [ 12 , 15 , 16 ]. Studies have shown that grass swale can be used as a stormwater mitigation strategy which reduces the pressure on the existing sewer system by retaining a large amount of rainfall runoff [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grass swales are vegetated open channels usually designed to convey runoff, reduce rainfall runoff by infiltration and boost the runoff quality from filtration through the soil media [ 11 , 12 , 13 , 14 , 15 ]. Grass swale uses different kind of vegetation, which can infiltrate the surface water into the underground soil [ 12 , 15 , 16 ]. Studies have shown that grass swale can be used as a stormwater mitigation strategy which reduces the pressure on the existing sewer system by retaining a large amount of rainfall runoff [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grass swale uses different kind of vegetation, which can infiltrate the surface water into the underground soil [ 12 , 15 , 16 ]. Studies have shown that grass swale can be used as a stormwater mitigation strategy which reduces the pressure on the existing sewer system by retaining a large amount of rainfall runoff [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…If soil permeability and contaminant removal is maintained, swales present a conveyance capability that efficiently promotes pollutant removal without posing a risk to underlying groundwater. However, nitrates could have a potential impact on groundwater due to increased soil concentration over time, but a filter bed beneath swales can provide a safeguard and frequent inspections are recommended [47].…”
Section: Filter Strips and Vegetated Swalesmentioning
confidence: 99%
“…Deux noues ont été aménagées fin 2016 au sein de box étanches (7 Â 4 Â 1,6 m) situés sur la plateforme d'essai du CSTB, Aquasim. La méthode de construction de la première noue (notée REF pour « référence ») vise à reproduire le terrassement d'un terrain naturel, donnant une noue « standard » capable de réguler le transport du ruissellement vers l'aval (Revitt et al, 2017). Cette dernière est constituée de sol excavé sur site, caractérisé comme un loam limoneux dans la classification texturale internationale (FAO, 2006).…”
Section: Materiels Et Méthodes 21 Dispositif Piloteunclassified